2013
DOI: 10.1182/blood-2012-06-434621
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophage Wnt-Calcineurin-Flt1 signaling regulates mouse wound angiogenesis and repair

Abstract: Key Points Macrophage Wnt signaling regulates wound angiogenesis and repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…Consistent with this, deletion of VEGF expression in macrophages severely reduced angiogenesis in open murine excisional wounds [84]; however, more recent studies indicate that macrophages can also have a "dampening" role on wound angiogenesis via noncanonical Wnt signalling and activation of Flt1 (a non-signalling VEGF receptor), which acts to suppress VEGF-mediated angiogenesis [85]. Also, a study in RhoB null mice showed that this non-constitutively expressed small GTPase, acting via VEZF1, is necessary for wound blood vessel sprouting, and that coincident with reduced wound angiogenesis in KO mouse wounds, there was enhanced lymphangiogenesis, which is normally much delayed by comparison to blood vessel sprouting [86].…”
Section: Wound Angiogenesismentioning
confidence: 68%
“…Consistent with this, deletion of VEGF expression in macrophages severely reduced angiogenesis in open murine excisional wounds [84]; however, more recent studies indicate that macrophages can also have a "dampening" role on wound angiogenesis via noncanonical Wnt signalling and activation of Flt1 (a non-signalling VEGF receptor), which acts to suppress VEGF-mediated angiogenesis [85]. Also, a study in RhoB null mice showed that this non-constitutively expressed small GTPase, acting via VEZF1, is necessary for wound blood vessel sprouting, and that coincident with reduced wound angiogenesis in KO mouse wounds, there was enhanced lymphangiogenesis, which is normally much delayed by comparison to blood vessel sprouting [86].…”
Section: Wound Angiogenesismentioning
confidence: 68%
“…The importance of Wnt ligands as developmental regulators of cell proliferation, migration, differentiation, and polarity are well known. In addition, recent reports suggest inhibitory roles of myeloid derived Wnt5a in developmental angiogenesis and wound repair (24,47). Surprisingly, Wnt5a was highly expressed in ischemic hind limb muscle of Glrx TG compared with WT control.…”
Section: Discussionmentioning
confidence: 97%
“…In myeloid cells, Wnt5a induction of sFlt is likely through nuclear factor of activated T cells (NFAT) activation (47). Interestingly, the interaction between NFAT and NF-B p65 promotes synergistic activation of NFAT (54).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, evidence for noncanonical Wnt signaling during angiogenesis is only beginning to emerge (Masckauchan et al, 2006;Cirone et al, 2008;Descamps et al, 2012). On the one hand, non-canonical Wnt ligands have been shown to suppress angiogenesis during retinal vascularization and wound healing (Stefater et al, 2011(Stefater et al, , 2013. On the other hand, Wnt5a has been described as a pro-angiogenic factor promoting EC proliferation, migration, survival and network formation (Masckauchan et al, 2006;Cirone et al, 2008;Descamps et al, 2012).…”
Section: Introductionmentioning
confidence: 99%